IMMUNOPATHOGENESIS OF HIV INFECTION: THE COMPLEX ROLE OF THE IMMUNE SYSTEM IN DISEASE DEVELOPMENT AND CONTROL - Debie Anggraini (Nusantara Hasana Journal, 2023)
Human immunodeficiency virus (HIV) infection remains a global challenge in public health, and a deeper understanding of its immunopathogenesis is essential for the development of more effective therapies and more efficient vaccines. the complexity of the interaction between HIV and the human immune system leads to a diverse course of the disease. Explanation of the main role of immune system components in detecting and responding to HIV infection, with special emphasis on the role of CD4+ T cells and the evation mechanisms applied by the HIV virus to avoid destruction by the immune system as well as the impact of HIV infection on dendritic cells, which play an important role in antigen presentation and initiation of immune response. We discuss how HIV utilizes dendritic cells for more efficient dissemination in the body and its impact on specific immunity. By integrating an in-depth understanding of the interaction between HIV and the immune system, this article aims to provide comprehensive insight into the immunopathogenesis of HIV infection and highlight future research directions to combat the disease. A better understanding of these complexities will hopefully support more effective HIV prevention and control efforts in the future.